Procedural Effects On Controlling Natural Disasters (Landslides And Flash Floods) Based On Environmental Degradation From Development In Malaysia - Hipeny, Alya Batrisyia (Universiti Sains Malaysia, 2022)
In recent years, Malaysia's growing population and accelerating economic conditions have resulted in the construction of high-rise condominiums and the expansion of settlements and lifelines across hilly areas. Natural disasters are always happening in Malaysia, with landslides and flash floods as the main problems and common natural disasters. This problem occurs annually due to rising numbers of development in Malaysia involving land clearance and rapid construction, especially in hilly areas. Under such circumstances, research was conducted on landslide and flash flood incidences in Malaysia from 2020 until 2022. The assessment in this research was done using the matrix method commonly used in Environmental Impact Assessment (EIA). The results gained by using those method shows that both landslides and flash flood naturally happen in the last quarter of a year, which are in December and January for both landslides and flash flood disaster. The highest score for landslide incidences was in Putrajaya and Kuala Lumpur with 8.4; in contrast, 9.2, the highest average score recorded for flash floods, happened in Selangor, Pahang, Kelantan, Kuala Lumpur, Melaka, Negeri Sembilan, Perak, and Terengganu. Both of these incidences occurred in December 2021. This situation shows that both natural and man-made affect the occurrence of the tragedy in Malaysia. Heavy rainfall and rapid development lead to this problem. Compliance with general guidelines from contractors, developers and agencies may reduce the number of these disasters in the future. Hence, it will help to prevent soil erosion and slope failure that frequently occurs in Malaysia.